General aspects and peculiarities about Cassava (Manihot esculenta Crantz) / Aspectos gerais e peculiaridades sobre mandioca (Manihot esculenta Crantz) - Luiz Eduardo Bezerra Silva; Joice Késsia Barbosa dos Santos; João Pedro Ferreira Barbosa; Luan Lucas Cardoso Lima; José Crisólogo de Sales Silva (Universidade Estadual de Alagoas, 2018)
Cassava is a perennial and woody tropical plant, adapted to soils of low fertility, and can be propagated by cuttings or seeds (VIANA et al., 2002). It stands out because it is a plant that adapts to soils of low fertility, however, it is a plant with high capacity of production of energetic substances. The objective of this review was to elucidate little-known characteristics and characteristics of cassava, improving the knowledge of the urban and rural population. For the elucidation, the research was done with bibliographical research on the economic importance, climate, soil, cassava utilization in animal feed, silage, cassava and cassava by - products in animal feed, as well as fertilization and the nutrients present in manioc leaf. In this way, it is important to know the characteristics and peculiarities that surround the cassava, so that there is a more adequate use of its parts, besides being able to optimize its cultivation.